2009
DOI: 10.1007/s10549-008-0299-4
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effects of protein kinase C beta1 (PKCβ1) and PKCε in the metastatic potential of a breast cancer murine model

Abstract: In this paper we investigated whether protein kinase C (PKC) beta1 and PKCepsilon, members of the classical and novel PKC family, respectively, induce phenotypic alterations that could be associated with tumor progression and metastatic dissemination in a murine model of breast cancer. Stable overexpression of PKCbeta1 in LM3 cells altered their ability to proliferate, adhere, and survive, and impaired their tumorigenicity and metastatic capacity. Moreover, PKCbeta1 induced the re-expression of fibronectin, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 52 publications
2
20
0
Order By: Relevance
“…PKCε is known to mediate proliferation in a number of cancer cells, such as lung and breast cancer cellular models (12, 13, 16). When we examined the effect of silencing PKCε on the growth properties of PC3-ML cells in culture, we noticed only a marginal reduction in cell number in PC3-ML-KDε1 and PC3-ML-KDε2 cells relative to control cell lines (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PKCε is known to mediate proliferation in a number of cancer cells, such as lung and breast cancer cellular models (12, 13, 16). When we examined the effect of silencing PKCε on the growth properties of PC3-ML cells in culture, we noticed only a marginal reduction in cell number in PC3-ML-KDε1 and PC3-ML-KDε2 cells relative to control cell lines (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, PKCε overexpression has been associated with elevated incidence of spontaneous and experimental metastases in mouse models. For example, overexpression of PKCε enhances spontaneous lung metastasis of breast cancer cells (16), and targeted transgenic overexpression of PKCε in skin promotes the development of squamous cell carcinomas which rapidly metastasize to regional lymph nodes (15). Our results in PC3-ML cells, revealed significant roles for PKCε in invasion regardless of a lack of involvement in cell motility and Rac activity, possibly highlighting distinctive roles for PKCε in different cellular models.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to this, Grossoni's group has reported that overexpression of PKC 1 in the breast cancer cell line LM3 actually reduces cell growth and expression of the metastasis-related proteases, uPA, and MMP-2 [62]. Thus, further research is required to decipher the true function of the PKC 1 and PKC 1I isozymes in breast cancer.…”
Section: Pkc Isozymes and Cancermentioning
confidence: 96%
“…Its expression was found to be a predictor of poorer overall and disease-free survival in breast cancer patients [51]. Conversely, its depletion led to a less aggressive phenotype in vitro as well as in xenograft models [51,52]. PKCɛ expression also correlated with tumor grade in prostate tumor samples [53].…”
Section: Pkcɛ In Metastasismentioning
confidence: 99%